Writing literature reviews a guide for students of the social and behavioral sciences - Galvan, Jose L.; Galvan, Melisa (Routledge, 2017)
This useful guide educates students in the preparation of literature reviews for term projects, theses, and dissertations. The authors provide numerous examples from published reviews that illustrate the guidelines discussed throughout the book.